Interstitial fibrosis is the critical determinant of impaired renal function in transplant glomerulopathy. (July 2016) - Toki, Daisuke; Inui, Masashi; Ishida, Hideki; Okumi, Masayoshi; Shimizu, Tomokazu; Shirakawa, Hiroki; Omoto, Kazuya; Unagami, Kohei; Setoguchi, Kiyoshi; Koike, Junki; Honda, Kazuho; Yamaguchi, Yutaka; et al.
Abstract: Aim: Transplant glomerulopathy (TG) is a feature of chronic antibody‐mediated injury in the glomerular capillaries in renal transplant recipients. TG is generally associated with proteinuria; however, renal function at the diagnosis of TG varies. This study aimed to determine which morphological abnormalities are associated with renal function and proteinuria at the diagnosis of TG. Methods: A total of 871 renal transplantations were performed at Tokyo Women's Medical University between 2005 and 2013. TG was diagnosed in 127 biopsies from 58 (6.7%) recipients. Renal function was evaluated by the estimated glomerular filtration rate (eGFR). Proteinuria was assessed by a dipstick test: positive for +1 and over. Results: At diagnosis, of 127 biopsies, 72, 37, and 18 had mild, moderate, and severe TG (Banff cg). The severity of TG was not associated with decreased eGFR at the time of biopsy (cg1: 36.1 ± 14.8, cg2‐3: 38.8 ± 14.5 mL/min per 1.73 m 2, P = 0.25), whereas the severity of interstitial fibrosis (IF) (Banff ci) was significantly associated with decreased eGFR (ci0‐1: 42.75 ± 13.32, ci2‐3: 27.69 ± 11.94 mL/min per 1.73 m 2, P < 0.0001). The multivariate analysis revealed that IF was the only independent risk factors for decreased eGFR (OR = 4.38, P = 0.0006). Meanwhile, TG was identified as the only independent risk factor for the incidence of proteinuria (OR = 2.67, P = 0.014). Conclusion: Interstitial fibrosis was a critical determinant of impaired renal function at the diagnosis of TG. The severity of TG was significantly associated with proteinuria, but did not contribute to renal dysfunction.